Telomere Attrition in Induced Pluripotent Stem Cell-Derived Neurons From ALS/FTD-Related C9ORF72 Repeat Expansion Carriers - Robinson, Hayley; Ali, Sk Imran; Diaz-Hernandez, Martha Elena; Lopez-Gonzalez, Rodrigo (Frontiers in Cell and Developmental Biology, 2022)
The GGGGCC (G4C2) repeat expansion in C9ORF72 is the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Dysregulated DNA damage response and the generation of reactive oxygen species (ROS) have been postulated as major drivers of toxicity in C9ORF72 pathogenesis. Telomeres are tandem-repeated nucleotide sequences that are at the end of chromosomes and protect them from degradation. Interestingly, it has been established that telomeres are sensitive to ROS. Here, we analyzed telomere length in neurons and neural progenitor cells from several induced pluripotent stem cell (iPSC) lines from control subjects and C9ORF72 repeat expansion carriers. We found an age-dependent decrease in telomere length in two-month-old iPSC-derived motor neurons from C9ORF72 carriers as compared to control subjects. This age-dependent decrease in telomere length was correlated with an increase in ROS, suggesting that ROS contribute to chromosome attrition in G4C2-related ALS/FTD.